2019
DOI: 10.7717/peerj.6978
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic study of the mechanism of anoikis resistance in head and neck squamous carcinoma

Abstract: Background Normal epithelial cells rapidly undergo apoptosis as soon as they lose contact with the extracellular matrix (ECM), which is termed as anoikis. However, cancer cells tend to develop a resistance mechanism to anoikis. This acquired ability is termed as anoikis resistance. Cancer cells, with anoikis resistance, can spread to distant tissues or organs via the peripheral circulatory system and cause cancer metastasis. Thus, inhibition of anoikis resistance blocks the metastatic ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…EMT is the initial step of cancer invasion, dissemination, and metastasis, during which epithelial cells loss adhesion between tumor cells and the extracellular matrix (ECM) to acquire mesenchymal characteristics and invasive abilities [14,20]. Accumulating evidence has now indicated that EMT is one of the critical mechanisms that confers cancer cells resistance to anoikis [21][22][23][24][25], then creates a favorable opportunity for tumor proliferation, invasion, and metastasis [26]. It has been demonstrated that PI3K/AKT pathway is a major downstream pathway of miR-145-5p, which is involved in the regulation of invasion and metastasis in different tumor types, mainly in squamous cell carcinoma, bladder cancer and NSCLC [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is the initial step of cancer invasion, dissemination, and metastasis, during which epithelial cells loss adhesion between tumor cells and the extracellular matrix (ECM) to acquire mesenchymal characteristics and invasive abilities [14,20]. Accumulating evidence has now indicated that EMT is one of the critical mechanisms that confers cancer cells resistance to anoikis [21][22][23][24][25], then creates a favorable opportunity for tumor proliferation, invasion, and metastasis [26]. It has been demonstrated that PI3K/AKT pathway is a major downstream pathway of miR-145-5p, which is involved in the regulation of invasion and metastasis in different tumor types, mainly in squamous cell carcinoma, bladder cancer and NSCLC [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, integrin-α2β1/-α5β1 interacted with epidermal growth factor receptor (EGFR) in the AR of colon cancer [29]. MiR-141/KLF12/Sp1/survivin signaling pathway enhanced AR in ovarian cancer, and a transcriptomic study addressed the importance of CDKN1A-regulated quiescence for cells to survive from anoikis in head and neck squamous carcinoma [30,31]. In accordance with the discoveries in previous studies, FASN, an enzyme implicated in the process of metabolism, has shown to be positively correlated with the development of various cancers, including GC [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…[19] The cause of anoikis resistance in HNSCC has been the subject of numerous research. [18] The process of epithelium cells changing into mesenchymal cells in response to certain normal and pathogenic stimuli is a frequent event in the development of HNSCC and is referred to as epithelial-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Anoikis resistance in HNSCC was found to be associated with the VEGFA-STAT3-KLF4-CDKN1A signaling pathway. [18] Anoikis resistance in HNSCC has also been linked to fibronectin. [19] The cause of anoikis resistance in HNSCC has been the subject of numerous research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation